2017
DOI: 10.1186/s12929-017-0385-1
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid alters cell fate commitment of human neural progenitors in a WNT/β-catenin/ROS signaling dependent manner

Abstract: BackgroundImproving the neuronal yield from in vitro cultivated neural progenitor cells (NPCs) is an essential challenge in transplantation therapy in neurological disorders. In this regard, Ascorbic acid (AA) is widely used to expand neurogenesis from NPCs in cultures although the mechanisms of its action remain unclear. Neurogenesis from NPCs is regulated by the redox-sensitive WNT/β-catenin signaling pathway. We therefore aimed to investigate how AA interacts with this pathway and potentiates neurogenesis.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 63 publications
(111 reference statements)
1
14
0
Order By: Relevance
“…In this study, we showed for the first time that hemozoin-induced damage to differentiated human neural progenitor cells is accompanied by marked induction of oxidative stress. These results are consistent with previous reports showing that oxidative stress mediates toxicity to human neural progenitor cells (Rharass et al 2017; Chang et al 2013). Remarkably, our experiments showed hemozoin induced caspase-6 activation in differentiated ReNcell VM human neural progenitor cells.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, we showed for the first time that hemozoin-induced damage to differentiated human neural progenitor cells is accompanied by marked induction of oxidative stress. These results are consistent with previous reports showing that oxidative stress mediates toxicity to human neural progenitor cells (Rharass et al 2017; Chang et al 2013). Remarkably, our experiments showed hemozoin induced caspase-6 activation in differentiated ReNcell VM human neural progenitor cells.…”
Section: Discussionsupporting
confidence: 94%
“…Hence, although not elucidated in detail up to date, AA may influence tenascin-C gene expression by other regulatory pathways than PDGF-BB does; and JAK/STAT pathway may play a role. In addition, AA has been reported to act via Wnt signaling [81,82], but the regulation of tenascin-C expression by the Wnt/β-catenin signaling pathway has not been reported for tenocytes yet, but only for macrophages [83] or smooth muscle cells [84].…”
Section: Discussionmentioning
confidence: 99%
“…Like other vitamins (ascorbic acid, calcitriol and retinoic acid) [ 118 , 119 , 120 , 121 , 122 ], nicotinamide affects neurogenesis by accelerating differentiation of embryonic stem cells or neural progenitors into post-mitotic neurons [ 123 , 124 ]. In vitro vitamin supplementation promotes progression of undifferentiated stem cells to neural progenitors, which further mature into efficient GABAergic neurons; the pro-inducing action is time-dependent as the effects are more pronounced when the vitamin is early received early (day 0) [ 124 ].…”
Section: Niacin In the Central Nervous Systemmentioning
confidence: 99%